2001
DOI: 10.1103/physrevd.63.045022
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of periodic potentials

Abstract: The renormalization of the periodic potential is investigated in the framework of the Euclidean onecomponent scalar field theory by means of the differential RG approach. Some known results about the sine-Gordon model are recovered in an extremely simple manner. There are two phases: an ordered one with asymptotical freedom and a disordered one where the model is nonrenormalizable and trivial. The order parameter of the periodicity, the winding number, indicates spontaneous symmetry breaking in the ordered pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 51 publications
(120 citation statements)
references
References 31 publications
4
115
1
Order By: Relevance
“…This gives a clear explanation in the FRG framework of the presence or the lack of SSB in O(N ) models in d = 2. Of course, the fact that there is no SSB for N = 2 does not imply the absence of the Berezinskii Kosterlitz-Thouless transition [59,60], as can be seen also in FRG treatments [10,[61][62][63].…”
Section: =mentioning
confidence: 99%
“…This gives a clear explanation in the FRG framework of the presence or the lack of SSB in O(N ) models in d = 2. Of course, the fact that there is no SSB for N = 2 does not imply the absence of the Berezinskii Kosterlitz-Thouless transition [59,60], as can be seen also in FRG treatments [10,[61][62][63].…”
Section: =mentioning
confidence: 99%
“…The renormalization of a two-dimensional one-component scalar field theory with a periodic self-interaction, and the two-dimensional generalized sine-Gordon model (GSGM) have been investigated for d = 2 dimensions in great detail over the last three decades [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15]. Here, we only mention some of the main results:…”
Section: Introductionmentioning
confidence: 99%
“…• The blocked potential for the two-dimensional GSGM tends to a constant effective potential in the IR limit, independent of the field [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…As we have shown previously in section 3.1 , the multi-color QCD 2 gives values of the parameter β 2 = 4π < β 2 c (N ) for arbitrary number N > 1 of colors, which means that the corresponding SG model is in the symmetry broken phase. Earlier calculations based on Fourier expansion [31,46,[56][57][58] showed that in the symmetry broken phase the effective potential is superuniversal with the parabolic shape (3.8). It happened numerically that the Fourier-expansion drove the evolution towards the pole at a non-vanishing scale.…”
Section: Jhep01(2011)126mentioning
confidence: 99%
“…The functional RG method showed [31,32,56,57] that this SG model has two phases depending on the value of its parameter β 2 /3. As we have shown previously in section 3.1 , the multi-color QCD 2 gives values of the parameter β 2 = 4π < β 2 c (N ) for arbitrary number N > 1 of colors, which means that the corresponding SG model is in the symmetry broken phase.…”
Section: Jhep01(2011)126mentioning
confidence: 99%